Macroeconomic fluctuations under natural disaster shocks in Central America and the Caribbean - Allan Wright; Patrice Borda (Inter-American Development Bank (IDB), 2016)
This paper examines the role of disaster shock in a one-sector, representative agent dynamic stochastic general equilibrium model (DSGE). First, it estimates a panel vector autoregresive (VAR) model for output, investment, trade balance, consumption, and country spread to capture the economic effects of output, country risk, and exogenous natural disaster shocks. The study determines the empirical dynamic responses of ten Caribbean countries and seven countries in Central America. Second, by taking into account rare events and trend shocks, this paper also provides a baseline framework of the dynamic interactions between the macroeconomic effects of rare events and financial friction for two specific countries: Barbados and Belize. Similar findings between empirical and general frameworks show that disaster shocks in Central America and the Caribbean have only a significative impact in the short-run regional business cycle. The findings show that Caribbean countries are better prepared for natural disaster shocks.
Keywords: E32; F41; 330; Panel VAR; Business Cycles; DSGE; Small Open Economy